PERBANDINGAN KADAR BIOMARKER FUNGSI KUOGULASI TIKUS PUTIH (Rattus norvegicus) BERDASARKAN VARIASI DIET VEGETARIAN - Arwan Bin Laeto; Rara Inggarsih; Septi Purnamasari; Masayu Farah Diba (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Coagulation is an important physiological mechanism of the body to maintain optimal function of recovery. The success of this mechanism is determined by normal levels of biomarkers are involved, such as platelets. Deficiency of levels of these biomarkers can cause diseases, such as dengue fever, shock and hemophilia. Diet provides biochemical elements that the body can then use to synthesize platelets in the blood. The purpose of study was to compare the levels of biomarkers of coagulation function in white rats (Rattus norvegicus) with a variety of vegetarian diets. The method of study was using in vivo experimental research. The dependent variable is the level of platelets and the independent variable is a variety of vegetarian diets (quasi, lacto-ovo and vegan). The sampling technique used the Federer formula with are samples of 28 white rats. Statistical test using T test and Wilcoxon test. The research data showed that giving a vegetarian diet caused significant changes in platelet levels in the quasi, lacto-ovo and vegan vegetarian diet groups with a significant value for each group, namely p = 0.026, p = 0.042 and p = 0.001. While on the standard diet there was no significant change in platelet levels (p=0.291). On average, the highest platelet levels were found in the quasi-vegetarian diet group and the lowest in the standard diet group. In conclusion, the quasi-vegetarian, lacto-ovo and vegan diets affects the levels of blood coagulation biomarkers (platelets) in white rats